The Advancement of Technology and its Impact on Social Life in Indonesia - Fransisca, Vika; Ningsih, Widia (Devotion : Journal of Research and Community Service, 2023)
Technological advances have had a significant impact on social life in Indonesia. One of the most significant impacts of technological advances in Indonesia is the emergence of social media. The emergence of social media has had a major impact on the way Indonesian people interact with each other. This research aims to find out the impact of the influence of technological advances on social life in Indonesia. This research uses a qualitative research method, while the data collection technique is done by literature study. Then the data that has been collected is analyzed descriptively. The results showed that technological advances have had a major impact on social life in Indonesia, one of which is changing the way people interact in social life. This is because social media has enabled people to connect over long distances, facilitating communication and collaboration between people who may never meet. In addition to changing the way people interact with each other, technological advancements also create new challenges that must be overcome to ensure that all Indonesians can benefit from these technological advancements.